Chickpea Value Chain in Bundelkhand Region of India: An Empirical Insight - Uma Sah, Vikrant Singh, Jitendra Ojha, Mohit Katiyar; S. K. Dubey; S. K. Singh, Prasoon Verma (Indian Journal of Extension Education, 2022)
The study mapped the chickpea value chains in Bundelkhand region of Uttar Pradesh (BRUP) state during 2019-21. Findings showed that chickpea production was profitable in the region for producers with B:C ratio of 2.15. The average production cost of chickpea was Rs. 23191/ha with an average net return of Rs. 26809/ha. Chickpea was primarily furthered as chickpea split grains (dal), flour (besan), and wholegrain. Four marketing channels were recorded with a series of actors involved in moving chickpea and its products from producers to consumers. The total value added collectively by different value chain actors varied from Rs 1929 to Rs. 3231/q depending upon the channels and chickpea products. Processors added maximum value (Rs 849/q to1689/q), followed by wholesalers (Rs. 475/q to Rs.745/q) across all the channels. The ME of MC was higher across all the channels and products giving a higher share to producers in consumer rupee (58.7 to 69.7 percent). Chickpea value chains are long and complex in the region. The establishment of farmers’ managed market platforms facilitating the aggregation of produce at the village level is suggested.